Kontribusi kegiatan ekstrakurikuler paduan suara terhadap peningkatan prestasi akademik di tingkat sekolah menengah - Berliana Safitri; Sherly Nurhikmah; Putri Dyah Indriyani (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This study aims to investigate the relationship between students' participation in choir extracurricular activities and the improvement of their academic achievement. Extracurricular activities are believed to not only enrich students’ social and emotional experiences but also positively influence their concentration, discipline, and learning motivation, which ultimately contribute to better academic performance. This research employs a quantitative approach with a correlational method. The population includes students actively involved in choir activities at a public senior high school in Bjms. A purposive sample of 50 students was selected for the study. Data were collected through a questionnaire measuring the level of extracurricular participation and documentation of students' latest academic scores. The data were analysed using Pearson Product-Moment correlation with the assistance of statistical software. The findings reveal a positive and significant correlation between the level of participation in choir activities and students’ academic achievement. The higher the frequency and intensity of student involvement in choir extracurricular activities, the better their academic performance tends to be. The study concludes that schools should provide stronger support for extracurricular development, particularly choir programs, as these activities can serve as a means of character building and holistic academic enhancement for students.